2014
DOI: 10.4314/jae.v18i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Green River Project Fish Farming Technologies by Farmers in Niger Delta Region of Nigeria

Abstract: The study assessed adoption of improved fish farming technologies by fish farmers as well as socioeconomic characteristics of respondents, level of adoption of GRP fish farming technologies and constraints to adoption of the technologies. The hypothesis of the study was that socioeconomic conditions of farmers do not significantly influence adoption of GRP technologies. Multistage sampling technique was used to select 120 respondents from two states in Niger Delta. Descriptive statistics, regression analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…However results from linear multiple regression analysis showed that older freshwater pond farmers have higher level of GAqP than the younger farmers. These results are consistent with findings by Ogbonna et al (2014) which have found the same result and also have stated that older farmer were in their economical stage. This economical stage factor will give an impact on decision making in technology adoption.…”
Section: Discussionsupporting
confidence: 93%
“…However results from linear multiple regression analysis showed that older freshwater pond farmers have higher level of GAqP than the younger farmers. These results are consistent with findings by Ogbonna et al (2014) which have found the same result and also have stated that older farmer were in their economical stage. This economical stage factor will give an impact on decision making in technology adoption.…”
Section: Discussionsupporting
confidence: 93%
“…The goal of the project is to increase agricultural productivity and to prevent further deterioration of the soil through the use of better farming techniques; improve the income of farmers and make them more self-sufficient and increase the standard of living of rural families so as to reduce the flow of migrants to the towns [7,8]. To achieve these objectives, the technologies they have disseminated to the farmers over many years include the fish farm management technologies, feeding techniques, fish culture management techniques, pond water quality and quantity management and liming techniques [9]. This study sought to ascertain the roles of the extension education of GRP in achieving agricultural development in the area.…”
Section: Introductionmentioning
confidence: 99%
“…Other sources are family members, neighbour farmers, extension services, input providers and mass media [14]. Personal experience, workshops and seminars, training, friends and neighbours, Ministry of agriculture, magazines of agriculture, extension officers, local Government officers, Non-Governmental Organizations and posters [15]. However, the information been disseminated through the information access points depend on the information needs of the fisher.…”
Section: Introductionmentioning
confidence: 99%